Biomimetic alloxan-catalyzed intramolecular redox reaction with O2: One-pot atom-economic synthesis of sulfinyl-functionalized benzimidazoles. (5th January 2021) - Zhang, Shiqi; Yi, Dong; Li, Guangxun; Li, Ling; Zhao, Gang; Tang, Zhuo
Graphical abstract: Highlights: Developing biomimetic alloxan-catalyzed intramolecular redox reaction with O2 . The process underwent two oxidations under mild and metal-free reaction conditions. The environmentally benign molecular oxygen as the only sacrificial reagent. One-pot atom-economic synthesis of various sulfinyl-functionalized benzimidazoles. Abstract: Given the necessity of sacrificial reductants in various biomimetic aerobic oxygenations, alloxan-catalyzed aerobic redox system for one-pot atom-economic synthesis of sulfinyl-functionalized benzimidazoles was developed by ingeniously binding both the substrate sulfide and sacrificial reductant. This mild and transition-metal-free protocol undergoes two oxidations without additional sacrificial reagents, except for the environmentally benign molecular oxygen.